(untitled) (Journal of actual problems of jurisprudence, 2018)
The article discusses some aspects of the problems and prospects of development of international tax law. Formation and development of international tax law – the basic regulatory control of tax relations at the international level has generated enormous interest in the scientific world, while at the same time has generated a lot of discussion among scientists about the nature of this phenomenon. A variety of views expressed and positions can be reduced to two basic concepts. Key words: taxes; taxation; international tax law; international tax relations.